MnZn-based ferrite

By adjusting the ratio of the basic components and auxiliary components of the MnZn system ferrite, its incremental permeability within a wide temperature range is optimized, the problem of insufficient incremental permeability in the prior art is solved, and the effect of high incremental permeability in the temperature range of -50 to 150°C is achieved.

CN119546562APending Publication Date: 2025-02-28JFE CHEMICAL CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202480002285.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-28
Filing Date
2024-06-19
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

It is difficult to achieve incremental permeability of more than 2300 in the wide temperature range of -50 to 150°C, especially when applying a DC magnetic field, especially for automotive use and PoE power supply, the incremental permeability is insufficient.

Method used

By adjusting the ratio of the basic components and auxiliary components of the MnZn-based ferrite, the content of Fe converted in Fe2O3 is ensured to be 52.0 mol% or more and 53.6 mol% or less, the content of Zn in ZnO is 10.1 mol% or more and less than 13.0 mol%, and an appropriate amount of Si, Ca, Co, Ti, Nb and V are added as auxiliary components to optimize the magnetic characteristics.

Benefits of technology

When a DC magnetic field of 25A/m is applied within a temperature range of -50~150°C, the incremental magnetic permeability reaches more than 2300; when a DC magnetic field of 50A/m is applied at 125°C, the incremental magnetic permeability reaches more than 1000, meeting the needs of automotive and PoE power supply purposes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Provided is a MnZn ferrite having a high incremental permeability over a wide temperature range. The MnZn ferrite according to the present invention comprises a base component, an auxiliary component, and unavoidable impurities, and the base component contains: Fe: 52.0-53.6 mol% inclusive in terms of Fe2O3, 0.5-1.5 mol% inclusive in terms of ZnO, and 0.5-1.5 mol% inclusive in terms of Mn, when the total of Fe, Zn, and Mn in terms of Fe2O3, ZnO, and MnO is 100.0 mol%; zn: 10.1 mol% or more but less than 13.0 mol% in terms of ZnO; the auxiliary components comprise, relative to the basic components, 30 to 200 ppm by mass of Si in terms of SiO2; ca: 300 to 1000 mass ppm in terms of CaO; co: 2100 to 3500 mass ppm in terms of Co < 3 > O < 4 >; ti: 2500 to 4000 mass ppm in terms of TiO2; nb: 50 to 500 mass ppm in terms of Nb2O5; and V: 0 to 500 ppm by mass in terms of V2O5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a MnZn ferrite, and in particular to a MnZn ferrite suitable for electronic components such as pulse transformers. Background Art

[0002] In the transformer of Ethernet (registered trademark) equipment, a pulse transformer using soft magnetic material in the magnetic core is used for the purpose of matching the impedance at the input and output terminals or maintaining electrical insulation. The pulse transformer is required to have high inductance, that is, high incremental permeability (μ) when a DC magnetic field is applied within a temperature range of, for example, -40 to 85°C. Δ Here, the incremental permeability is a value indicating the permeability (ease of magnetization) of the magnetic core when a magnetic field is applied. In addition, the incremental permeability and effective permeability have the same meaning, so they are uniformly expressed as incremental permeability in this specification.

[0003] In the magnetic core using soft magnetic materials, ring-shaped MnZn ferrite is usually used. MnZn ferrite is particularly easy to obtain high magnetic permeability and high inductance among many soft magnetic materials. In addition, MnZn ferrite has the advantages of being cheap compared to metal magnetic materials such as amorphous metals, and being stable because it is an oxide and does not rust.

[0004] However, MnZn-based ferrites are oxide magnetic materials and thus have low Curie temperatures and their magnetic properties vary greatly with temperature fluctuations. Therefore, compared with metal magnetic materials, it is difficult to obtain stable magnetic properties over a wide temperature range.

[0005] When a pulse transformer is used in a line terminal device, etc., it is sometimes installed outdoors, and the MnZn-based ferrite used in the pulse transformer needs to have a high initial magnetic permeability (μi) in a wide temperature range from low temperature to high temperature. In addition, in digital communication equipment, the pulse transformer is sometimes magnetized by the change of the positive and negative balance of the transmitted pulse voltage, and operates when a DC magnetic field is applied. Even when such a DC magnetic field is applied, a high inductance required for signal conversion, that is, a high incremental magnetic permeability, is required. In the above-mentioned applications, the size of the DC magnetic field applied will vary depending on the required inductance specifications, usage methods, etc., and a high incremental magnetic permeability is required at room temperature.

[0006] In the past, pulse transformers were widely used in civilian equipment, but in recent years, with the development of automobile networking, they are gradually being used in automobiles. In existing civilian equipment, they are required to work normally in the temperature range of 0 to 70°C, -40 to 85°C or -40 to 105°C, but in automobile use, they are required to work normally in a wider temperature range, such as -40 to 125°C or -50 to 150°C.

[0007] On the other hand, in Ethernet devices, there are also uses for PoE (Power over Ethernet) power supply such as PoE / PoE+ / PoE++ that directly supplies the driving power of the device together with the transmission signal. In this case, the pulse transformer is used under the condition of superimposing a current larger than the signal transmission. In addition, it can be considered that due to the increase in the output of PoE power supply, the popularization of SiC and GaN semiconductors, etc., the peripheral components in the device are heated, and therefore the use environment of the pulse transformer's magnetic core (core body) has moved to a higher temperature side. Therefore, the MnZn-based ferrite used in this application is required to be a material with high inductance, that is, high incremental permeability, at a higher temperature and high magnetic field superposition, even if the initial magnetic permeability μi is low.

[0008] The MnZn ferrite used in existing civilian equipment is mainly Fe 2 O 3 , ZnO, and MnO are the main components, and high magnetic permeability is exhibited in the main components that make the magnetic anisotropy constant and magnetostriction constant zero. Therefore, MnZn ferrites are used as small or thin magnetic cores for transformers, noise filters, etc. Although there is a problem that it is difficult to obtain stable magnetic properties over a wide temperature range, in order to correspond to civilian pulse transformers, a method of achieving high incremental magnetic permeability when a DC magnetic field is applied in a temperature range of -40 to 85°C or -40 to 105°C has been proposed. In addition, in this specification, the values ​​of initial magnetic permeability and incremental magnetic permeability are expressed as a ratio to the magnetic permeability μo of a vacuum (relative magnetic permeability).

[0009] Patent Documents 1, 2, and 3 propose ferrites having an incremental magnetic permeability of 2000 or more when a DC magnetic field is applied in a temperature range of -40 to 85°C. Patent Documents 4 and 5 propose MnZnCo ferrites having a high initial magnetic permeability in a wide temperature range of about -20°C to 150°C. Patent Document 6 proposes an MnZn ferrite having an initial magnetic permeability of 3000 or more at 23°C, a small rate of change of initial magnetic permeability from -20 to 150°C, and a saturation magnetic flux density of 540 mT or more at 23°C.

[0010] Patent Document 7 proposes a MnZn-based ferrite having an incremental magnetic permeability of 400 or more in the temperature range of 0°C to 85°C and an incremental magnetic permeability of 700 or more at 65°C under application of a large DC magnetic field of 80 A / m.

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: Japanese Patent Application Publication No. 2008-143745;

[0014] Patent Document 2: Japanese Patent Application Publication No. 2010-189247;

[0015] Patent Document 3: Japanese Patent Application Publication No. 2010-195596;

[0016] Patent Document 4: Japanese Patent Application Publication No. 2015-229625;

[0017] Patent Document 5: Japanese Patent Application Publication No. 2015-229626;

[0018] Patent Document 6: Japanese Patent Application Publication No. 2005-236069;

[0019] Patent document 7: Japanese Patent Application Publication No. 2010-173899. Summary of the invention

[0020] Problem that the invention aims to solve

[0021] However, the temperature ranges assumed in Patent Documents 1, 2, and 3 are all -40 to 85°C, and it is impossible to obtain an incremental permeability of more than 2300 in the temperature range of -50 to 150°C. Although the temperature ranges assumed in Patent Documents 4 and 5 are wide, the MnZnCo ferrites in Patent Documents 4 and 5 are used for noise filters, and the incremental permeability when a DC magnetic field is applied is not considered, and it is impossible to obtain an incremental permeability of more than 2300 in the temperature range of -50 to 150°C. Patent Document 6 records that the rate of change of the initial permeability is small in the temperature range of -20 to 150°C, but the incremental permeability when a DC magnetic field is applied is not considered, and it is impossible to obtain an incremental permeability of more than 2300 in the temperature range of -50 to 150°C.

[0022] In Patent Document 7, although a large DC magnetic field of 80 A / m is applied, the incremental permeability at 85°C is less than 1000. In the temperature range exceeding 85°C, it is impossible to obtain a practical level of incremental permeability of more than 1000.

[0023] To date, many MnZn ferrites for pulse transformers suitable for civilian equipment that can be used in the temperature range of -40 to 85°C have been proposed, but no MnZn ferrites suitable for LANs for automotive purposes, etc. that can be used in the temperature range of -50 to 150°C and have excellent incremental permeability when a DC magnetic field is applied in a wide temperature range have been proposed.

[0024] Furthermore, there is no suggestion of an MnZn-based ferrite suitable for PoE power supply that can be used in a temperature range exceeding 85° C. and that can obtain a high incremental permeability when a DC magnetic field of 50 A / m is applied.

[0025] Therefore, an object of the present invention is to provide a MnZn ferrite having a high incremental permeability in a wide temperature range, that is, an incremental permeability of 2300 or more when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C. In addition, another object of the present invention is to provide a MnZn ferrite having an incremental permeability of 1000 or more when a DC magnetic field of 50 A / m is applied at 125°C.

[0026] In addition, the incremental permeability is usually measured by applying a DC magnetic field of 25A / m to MnZn ferrite for general use, but in special cases where a DC magnetic field of 33A / m is applied as in Patent Documents 1, 2, and 3, it also exists depending on the use of the MnZn ferrite. In the present invention, the DC magnetic field applied when measuring the incremental permeability of MnZn ferrite for general use is 25A / m. In addition, the DC magnetic field applied when measuring the incremental permeability of MnZn ferrite for PoE power supply is 50A / m.

[0027] Solutions for solving problems

[0028] The inventors of the present invention have conducted intensive research to solve the above-mentioned problems, and have obtained the following findings. By containing prescribed amounts of Fe and Zn as basic components, the balance being Mn, and prescribed amounts of Si, Ca, Co, Ti, Nb, and V as auxiliary components, the incremental permeability when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C can be 2300 or more. In addition, the incremental permeability when a DC magnetic field of 50 A / m is applied at 125°C can be 1000 or more.

[0029] The main configuration of the present invention completed based on the above findings is as follows.

[0030] [1] A MnZn ferrite composed of a basic component, an auxiliary component and inevitable impurities,

[0031] In the 2 O 3 When the total of Fe, Zn and Mn calculated as ZnO and MnO is taken as 100.0 mol%,

[0032] The above basic ingredients include:

[0033] Fe: with Fe 2 O 3 The conversion is 52.0 mol% or more and 53.6 mol% or less;

[0034] Zn: 10.1 mol% or more and less than 13.0 mol% in terms of ZnO; and

[0035] Mn: remainder,

[0036] Relative to the above basic ingredients, the above auxiliary ingredients include:

[0037] Si: SiO 2 Converted to 30 mass ppm or more and 200 mass ppm or less;

[0038] Ca: 300 mass ppm or more and 1000 mass ppm or less in terms of CaO;

[0039] Co: Co 3 O 4 Converted to 2100 mass ppm or more and 3500 mass ppm or less;

[0040] Ti: TiO 2 Converted to 2500 mass ppm or more and 4000 mass ppm or less;

[0041] Nb: Nb 2 O 5 Calculated as 50 ppm by mass or more and 500 ppm by mass or less; and

[0042] V: V 2 O 5 The conversion is 0 mass ppm or more and 500 mass ppm or less.

[0043] [2] The MnZn ferrite according to [1] above, wherein V 2 O 5 The converted V content is 50 mass ppm or more and 250 mass ppm or less.

[0044] [3] The MnZn ferrite according to [1] above, wherein V 2 O 5 The converted V content is 100 mass ppm or more and 500 mass ppm or less.

[0045] [4] The MnZn-based ferrite according to [1] or [2] above, wherein the incremental magnetic permeability is 2300 or more when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C.

[0046] [5] The MnZn-based ferrite according to [1] or [3] above, wherein the incremental magnetic permeability when a DC magnetic field of 50 A / m is applied at 125°C is 1000 or more.

[0047] Effects of the Invention

[0048] According to the present invention, it is possible to obtain a MnZn ferrite having a high incremental permeability in a wide temperature range, that is, an incremental permeability of 2300 or more when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150° C. In addition, according to the present invention, it is possible to obtain a MnZn ferrite having an incremental permeability of 1000 or more when a DC magnetic field of 50 A / m is applied at 125° C. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1A This is a graph showing the incremental permeability of the inventive examples and comparative examples of the present invention when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C. Figure 1A Inventive Examples and Comparative Examples in which the content of Fe as a basic component was changed are shown.

[0050] Figure 1B This is a graph showing the incremental permeability of the inventive examples and comparative examples of the present invention when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C. Figure 1B Inventive Examples and Comparative Examples in which the content of Zn as a basic component was changed are shown.

[0051] Figure 2A This is a graph showing the incremental permeability of the inventive examples and comparative examples of the present invention when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C. Figure 2A Inventive Examples and Comparative Examples in which the content of Si as an auxiliary component was changed are shown.

[0052] Figure 2B This is a graph showing the incremental permeability of the inventive examples and comparative examples of the present invention when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C. Figure 2B Inventive Examples and Comparative Examples in which the content of Ca as an auxiliary component was changed are shown.

[0053] Figure 2C This is a graph showing the incremental permeability of the inventive examples and comparative examples of the present invention when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C. Figure 2C Inventive Examples and Comparative Examples in which the content of Co as an auxiliary component was changed are shown.

[0054] Figure 2D This is a graph showing the incremental permeability of the inventive examples and comparative examples of the present invention when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C. Figure 2D Inventive examples and comparative examples in which the content of Ti as an auxiliary component was changed are shown.

[0055] Figure 2EThis is a graph showing the incremental permeability of the inventive examples and comparative examples of the present invention when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C. Figure 2E Inventive Examples and Comparative Examples in which the content of Nb as an auxiliary component was changed are shown.

[0056] Figure 3 This is a graph showing the incremental permeability of the inventive examples and comparative examples of the present invention when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C. Figure 3 Inventive Examples and Comparative Examples in which the content of V as an auxiliary component was changed are shown.

[0057] Figure 4A This is a graph showing the incremental permeability of the inventive examples and comparative examples of the present invention when a DC magnetic field of 50 A / m is applied in a temperature range of -50 to 125°C. Figure 4A Inventive Examples and Comparative Examples in which the content of Ca as an auxiliary component was changed are shown.

[0058] Figure 4B This is a graph showing the incremental permeability of the inventive examples and comparative examples of the present invention when a DC magnetic field of 50 A / m is applied in a temperature range of -50 to 125°C. Figure 4B Inventive Examples and Comparative Examples in which the content of V as an auxiliary component was changed are shown. DETAILED DESCRIPTION

[0059] Hereinafter, an embodiment of the MnZn-based ferrite of the present invention will be described. In addition, the embodiment described below is an example of specific embodiment of the present invention, and the configuration of the present invention is not limited to this specific example.

[0060] [MnZn ferrite]

[0061] The MnZn ferrite of the present invention is composed of basic components, auxiliary components and inevitable impurities, and the oxides of Fe, Zn and Mn are the basic components. In addition, the following mol% is the composition ratio of the basic components.

[0062] (Basic Ingredients)

[0063] Fe 2 O 3 : 52.0 mol% or more and 53.6 mol% or less

[0064] The Fe contained in MnZn ferrite is Fe 2 O 3 When the conversion is less than 52.0 mol%, the incremental permeability is greatly reduced. Therefore, the Fe contained in the MnZn ferrite is Fe 2 O 3On the other hand, Fe contained in MnZn-based ferrite is Fe 2 O 3 When the conversion exceeds 53.6 mol%, the incremental permeability also decreases significantly. Therefore, the Fe contained in the MnZn ferrite is Fe 2 O 3 The conversion is 53.6 mol% or less, preferably 53.1 mol% or less. In addition, the Fe contained in the MnZn ferrite is Fe 2 O 3 When converted to about 53.0 mol%, the magnetostriction constant λ is 0, and the incremental permeability when a DC magnetic field is applied is the highest. 2 O 3 When converted to 53.0 mol %, that is, when λ=0, the core body expands and contracts due to the application of a magnetic field, thereby generating stress, which further hinders the movement of the magnetic domain wall and significantly reduces the incremental permeability.

[0065] ZnO: 10.1 mol% or more and less than 13.0 mol%

[0066] It is known that in MnZn ferrites, the Curie temperature and the secondary peak change depending on the ratio of Fe to Zn. If the content of Zn in the MnZn ferrite is 10.1 mol% or more and less than 13.0 mol% in terms of ZnO, the Curie temperature is approximately 200°C or more, and an incremental permeability in a high temperature range of up to 150°C can be obtained. In the case where the content of Zn in the MnZn ferrite is less than 10.1 mol% in terms of ZnO, although the Curie temperature becomes higher, the initial permeability when no DC magnetic field is applied decreases, resulting in a decrease in the incremental permeability in the entire temperature range when a DC magnetic field is applied. Therefore, the content of Zn in the MnZn ferrite is 10.1 mol% or more in terms of ZnO, preferably 10.2 mol% or more, more preferably 10.5 mol% or more, and even more preferably 11.0 mol% or more. On the other hand, when the Zn content in the MnZn ferrite is 13.0 mol% or more in terms of ZnO, the initial magnetic permeability when no DC magnetic field is applied becomes high, but the Curie temperature decreases, and the incremental magnetic permeability when a DC magnetic field is applied at 150° C. decreases. Therefore, the Zn content in the MnZn ferrite is less than 13.0 mol% in terms of ZnO, and preferably 12.9 mol% or less.

[0067] The Curie temperature of the MnZn ferrite of the present invention is preferably 190°C or higher, more preferably 200°C or higher, because a high incremental permeability when a DC magnetic field is applied can be obtained even at 150°C. The Curie temperature of the MnZn ferrite has no particular upper limit, but is usually 230°C or lower.

[0068] MnO: Balance

[0069] The Fe of the MnZn ferrite of the present invention 2 O 3 The total amount of ZnO and MnO is 100.0 mol%. In addition, the Mn contained in the MnZn ferrite is preferably 33.9 mol% or more in terms of MnO. In addition, the Mn contained in the MnZn ferrite is preferably 37.0 mol% or less in terms of MnO, and more preferably 36.9 mol% or less.

[0070] (auxiliary ingredients)

[0071] Next, the auxiliary components are described. The MnZn-based ferrite of the present invention contains Si, Ca, Co, Ti, and Nb as auxiliary components in addition to the above-mentioned basic components. Furthermore, it is preferred to contain V as an auxiliary component. These components are SiO 2 , CaO, Co 3 O 4 、TiO 2 , Nb 2 O 5 、V 2 O 5 The auxiliary component of the composition of the present invention is preferably SiO 2 , CaO, Co 3 O 4 、TiO 2 and Nb 2 O 5 Composed of, or made of SiO 2 , CaO, Co 3 O 4 、TiO 2 , Nb 2 O 5 and V 2 O 5 In the present invention, the content of the auxiliary components is the content relative to the basic components.

[0072] SiO 2 : 30 mass ppm or more and 200 mass ppm or less

[0073] SiO 2It is an additive that promotes the formation of grain boundaries, inhibits grain growth, increases resistivity, and reduces initial magnetic permeability. 2 , which can improve the incremental permeability in a wide temperature range of -50 to 150°C. The Si contained in MnZn ferrite is in the form of SiO 2 When the amount is less than 30 mass ppm, the incremental permeability in the low temperature range and high temperature range decreases, and it is difficult to obtain an incremental permeability of 2300 or more when a DC magnetic field is applied in a wide temperature range of -50 to 150°C. Therefore, Si contained in MnZn ferrite is in the form of SiO 2 The content of Si in the MnZn-based ferrite is 30 mass ppm or more, preferably 32 mass ppm or more, and more preferably 35 mass ppm or more. 2 When the content exceeds 200 mass ppm, the initial magnetic permeability is greatly reduced, and therefore the incremental magnetic permeability is also greatly reduced, making it difficult to obtain an incremental magnetic permeability of 2300 or more in a wide temperature range of -50 to 150°C. Therefore, Si contained in MnZn ferrite is in the form of SiO 2 The converted amount is 200 mass ppm or less, preferably 190 mass ppm or less, more preferably 150 mass ppm or less, and further preferably 49 mass ppm or less.

[0074] CaO: 300 mass ppm or more and 1000 mass ppm or less

[0075] CaO is an additive that promotes the formation of grain boundaries and inhibits grain growth, increases resistivity, and reduces initial magnetic permeability. By making MnZn ferrite contain an appropriate amount of CaO, the incremental magnetic permeability in a wide temperature range of -50 to 150°C can be increased. When the Ca contained in the MnZn ferrite is less than 300 mass ppm in terms of CaO, the incremental magnetic permeability in the low temperature range and the high temperature range decreases, and it is difficult to obtain an incremental magnetic permeability of 2300 or more when a DC magnetic field is applied in a wide temperature range of -50 to 150°C. Therefore, the Ca contained in the MnZn ferrite is 300 mass ppm or more in terms of CaO, preferably 390 mass ppm or more. On the other hand, when the Ca contained in the MnZn ferrite exceeds 1000 mass ppm in terms of CaO, the initial magnetic permeability is greatly reduced, so the incremental magnetic permeability is also greatly reduced, and it is difficult to obtain an incremental magnetic permeability of 2300 or more in a wide temperature range of -50 to 150°C. Therefore, the Ca content in the MnZn-based ferrite is 1000 mass ppm or less, preferably 950 mass ppm or less, and more preferably 840 mass ppm or less, in terms of CaO.

[0076] In the MnZn ferrite for PoE power supply, where the incremental permeability becomes important when a DC magnetic field of 50 A / m is applied at 125°C, a higher incremental permeability can be obtained by including more Ca. Therefore, in the MnZn ferrite for PoE power supply, the Ca contained in the MnZn ferrite is preferably 500 mass ppm or more, more preferably 600 mass ppm or more, further preferably 700 mass ppm or more, and most preferably 800 mass ppm or more in terms of CaO.

[0077] On the other hand, when the Ca contained in the MnZn ferrite exceeds 1000 mass ppm in terms of CaO, the initial magnetic permeability is excessively reduced, and the incremental magnetic permeability is also reduced accordingly, so the incremental magnetic permeability when a DC magnetic field of 50 A / m is applied at 125°C is less than 1000, which is not preferred. Therefore, even in the case of MnZn ferrite for PoE power supply, the Ca contained in the MnZn ferrite is 1000 mass ppm or less in terms of CaO, preferably 950 mass ppm or less.

[0078] Co 3 O 4 : 2100 mass ppm or more and 3500 mass ppm or less

[0079] Co 3 O 4 It is an effective additive for improving the temperature dependence of the magnetic properties of MnZn ferrite. 3 O 4 , the incremental permeability changes with respect to temperature when a DC magnetic field is applied become smaller, and the incremental permeability increases in the low temperature range and the high temperature range. 3 O 4 It also has the effect of shifting the temperature dependence of magnetic permeability to the low temperature side. Therefore, when the Co content is too little or too much, the balance of magnetic permeability in the low temperature range and the high temperature range is destroyed, and the incremental magnetic permeability in the low temperature range or the high temperature range is reduced, and it is impossible to obtain a high incremental magnetic permeability in a wide temperature range of -50 to 150°C. 3 O 4 When the amount of Co contained in MnZn ferrite is less than 2100 mass ppm, the maximum point of the temperature characteristic of the incremental permeability shifts to the high temperature side. Although the incremental permeability at high temperature increases, the characteristic at low temperature deteriorates, and the incremental permeability of more than 2300 cannot be obtained in a wide temperature range of -50 to 150°C. 3 O 4 On the other hand, the Co contained in the MnZn-based ferrite is Co.3 O 4 When the conversion exceeds 3500 mass ppm, the maximum point of the temperature characteristic of the incremental permeability shifts to the low temperature side. Although the low temperature characteristic of the incremental permeability becomes higher, the high temperature characteristic becomes worse, and the incremental permeability of more than 2300 cannot be obtained in a wide temperature range of -50 to 150°C. Therefore, the Co contained in the MnZn ferrite is Co 3 O 4 The converted amount is 3500 mass ppm or less, preferably 3200 mass ppm or less.

[0080] TiO 2 : 2500 mass ppm or more and 4000 mass ppm or less

[0081] TiO 2 It is an effective additive for increasing the incremental magnetic permeability of MnZn ferrite when a DC magnetic field is applied. 2 It has little effect on the crystal grain size of ferrite. 2 , the coercivity of ferrite decreases, and the slope of the demagnetization curve changes in the area where a magnetic field equivalent to a DC magnetic field of 25A / m is applied, thereby increasing the incremental permeability. 2 It also has the effect of shifting the temperature characteristics of the initial magnetic permeability and incremental magnetic permeability to the low temperature side. Therefore, if the content is not appropriate, the low temperature characteristics and high temperature characteristics will deteriorate, and it will not be possible to obtain an incremental magnetic permeability of more than 2300 in a wide temperature range of -50 to 150°C. The Ti contained in MnZn ferrite is TiO 2 When the content is less than 2500 mass ppm, the incremental permeability is insufficiently increased and the temperature characteristics are also shifted to the high temperature side, so it is impossible to obtain an incremental permeability of 2300 or more in a wide temperature range of -50 to 150°C. Therefore, the Ti contained in the MnZn ferrite is in the form of TiO 2 On the other hand, the Ti contained in the MnZn-based ferrite is in the form of TiO 2 When the conversion exceeds 4000 mass ppm, the temperature characteristics shift to the low temperature side. Although the reason is unknown, the incremental permeability when a DC magnetic field is applied also decreases sharply in the temperature range around -50°C, so it is impossible to obtain an incremental permeability of more than 2300. Therefore, the Ti contained in the MnZn ferrite is in the form of TiO 2 The amount is converted to 4000 mass ppm or less, preferably 3950 mass ppm or less, more preferably 3500 mass ppm or less, and further preferably 3300 mass ppm or less.

[0082] Nb2 O: 50 mass ppm or more and 500 mass ppm or less

[0083] Nb 2 O 5 It has the effect of inhibiting the formation of coarse grains and obtaining small and uniform grains, thereby improving the resistivity. By containing an appropriate amount of Nb, the incremental magnetic permeability when a DC magnetic field is applied can be improved. The Nb contained in MnZn ferrite is Nb 2 O 5 When the conversion is less than 50 mass ppm, the generation of coarse grains is not sufficiently suppressed, the resistivity is also reduced, and therefore the incremental permeability when a DC magnetic field is applied is also reduced. Therefore, the Nb contained in the MnZn ferrite is Nb 2 O 5 The amount of Nb contained in the MnZn-based ferrite is 50 mass ppm or more, preferably 75 mass ppm or more, more preferably 100 mass ppm or more, and further preferably 130 mass ppm or more. 2 O 5 When the Nb content exceeds 500 ppm by mass, the grain size becomes finer and the resistivity becomes higher, so that the domain wall becomes difficult to move and the initial magnetic permeability decreases. 2 O 5 The amount is converted to 500 mass ppm or less, preferably 475 mass ppm or less, and more preferably 400 mass ppm or less.

[0084] V 2 O 5 : 0 mass ppm or more and 500 mass ppm or less

[0085] V 2 O 5 Also with Nb 2 O 5 Similarly, it is an additive that suppresses the formation of coarse grains, obtains small and uniform grains, and improves the resistivity. By containing Nb and an appropriate amount of V, the incremental magnetic permeability when a DC magnetic field is applied can be appropriately increased. Therefore, in general applications in the temperature range of -50 to 150°C, the V contained in MnZn ferrite is 2 O 5 The content of V in the MnZn ferrite is 0 mass ppm or more, preferably 50 mass ppm or more, and more preferably 55 mass ppm or more. In addition, in PoE power supply applications where the incremental permeability when a DC magnetic field of 50 A / m is applied at 125°C becomes important, the V in the MnZn ferrite is 0 mass ppm or more, preferably 50 mass ppm or more, and more preferably 55 mass ppm or more. 2 O 5 It is 0 mass ppm or more, preferably 100 mass ppm or more, and more preferably 150 mass ppm or more.

[0086] On the other hand, in any application, the V contained in the MnZn ferrite is V 2 O 5 When the content exceeds 500 mass ppm, the grain size is reduced and the resistivity is increased, so the domain wall is difficult to move and the initial magnetic permeability is reduced. As a result, the incremental magnetic permeability is also reduced. Therefore, the V contained in the MnZn ferrite for general use is 2 O 5 The content of V contained in the MnZn-based ferrite for PoE power supply is 500 mass ppm or less, preferably 490 mass ppm or less, more preferably 480 mass ppm or less, and further preferably 250 mass ppm or less. 2 O 5 It is 500 mass ppm or less, preferably 400 mass ppm or less.

[0087] (Unavoidable impurities)

[0088] The composition of the MnZn ferrite of the present invention is composed of inevitable impurities in addition to the basic components and auxiliary components. As inevitable impurities, P, B, S, Cl, K, etc. can be cited, and the total content of these inevitable impurities is suppressed to below 500 mass ppm. The total content of inevitable impurities is preferably below 100 mass ppm, more preferably below 50 mass ppm.

[0089] (Initial permeability when no DC magnetic field is applied)

[0090] When a DC magnetic field is applied to MnZn ferrite, the initial magnetic permeability decreases, that is, the incremental magnetic permeability also decreases. Therefore, in order to obtain a high incremental magnetic permeability, it is important to increase the initial magnetic permeability when no DC magnetic field is applied in advance. In general-purpose MnZn ferrites in the temperature range of -50 to 150°C, when the initial magnetic permeability at 23°C when no DC magnetic field is applied is 3500 or more, a high incremental magnetic permeability of 2300 or more can be appropriately obtained within a wide temperature range of -50 to 150°C. Therefore, the initial magnetic permeability of MnZn ferrite at 23°C when no DC magnetic field is applied is preferably 3500 or more. On the other hand, there is no particular upper limit to the initial magnetic permeability at 23°C when no DC magnetic field is applied, and it is usually 5000 or less.

[0091] (Incremental permeability when a DC magnetic field of 25A / m is applied in the temperature range of -50 to 150°C)

[0092] The MnZn ferrite has the above composition, so that the incremental permeability when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C can be 2300 or more. There is no particular upper limit to the incremental permeability when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C, but it is usually 4500 or less.

[0093] (Incremental permeability when a DC magnetic field of 50A / m is applied at 125°C, for PoE power supply purposes)

[0094] In MnZn ferrite, if the applied DC magnetic field is increased, the incremental permeability will be greatly reduced, especially in the high temperature range, but the MnZn ferrite has the above composition, so that the incremental permeability when a DC magnetic field of 50 A / m is applied at 125°C can be made to be 1000 or more. There is no particular upper limit to the incremental permeability when a DC magnetic field of 50 A / m is applied at 125°C, and it is usually 2000 or less.

[0095] [Method for producing MnZn-based ferrite]

[0096] Next, the method for producing the MnZn ferrite of the present invention will be described. As the method for producing the MnZn ferrite of the present invention, a known general production method can be used.

[0097] An example of the method for producing the MnZn-based ferrite of the present invention is as follows: First, Fe as a basic component is weighed so as to have a content specified in the present invention. 2 O 3 , ZnO and Mn 3 O 4 (The composition ratio is not converted to Mn 3 O 4 The powder raw materials (which are converted to MnO for processing) are mixed by an attritor and a ball mill to obtain a mixed powder. The mixing method may be any of a dry method and a wet method. Then, the mixed powder is pre-calcined at 800 to 1000°C to obtain a pre-calcined powder. Next, the obtained pre-calcined powder is wet-pulverized by an attritor and a ball mill to obtain a pulverized powder with a particle size of about 0.8 to 1.6 μm. At this time, the oxide of the auxiliary component is added and pulverized in such a manner as to become the content specified in the present invention. During the pulverizing operation, homogenization is performed in such a manner that the concentration of the auxiliary component has no deviation. An organic binder such as polyvinyl alcohol is added to the obtained pulverized powder, and granulation is performed using a spray dryer or the like to obtain a granulated powder. Furthermore, the granulated powder is filled into a metal mold of a specified shape and molded to obtain a molded body. The obtained molded body is sintered at about 1100 to 1400°C to obtain a MnZn-based ferrite.

[0098] The MnZn ferrite thus obtained has a high characteristic of an incremental magnetic permeability of 2300 or more in a wide temperature range of -50 to 150°C when a DC magnetic field of 25A / m is applied. In addition, it has a high characteristic of an incremental magnetic permeability of 1000 or more when a DC magnetic field of 50A / m is applied at 125°C.

[0099] (Improvement of deviation)

[0100] For the existing MnZn ferrite for pulse transformers, the required upper limit temperature is as low as 85°C, and high initial magnetic permeability and high incremental magnetic permeability are required. Therefore, a large amount of compositions with high ZnO molar ratio and high initial magnetic permeability are used. Generally, it is known that Zn is easy to evaporate if sintered at high temperature. When using ferrite powder with high initial magnetic permeability (high ZnO molar ratio) to form a small ferrite core and sinter it, the problem of Zn evaporation from the core surface has received more attention. Due to the evaporation of Zn, there will be a slight deviation in the composition of the ferrite core surface and the inside of the ferrite core. Therefore, if ferrite powder with a high ZnO molar ratio is used, the deviation of the surface composition becomes larger, so there is a problem that the deviation of the initial magnetic permeability and incremental magnetic permeability also becomes larger. In contrast, in order to be able to be used in a wide temperature range of -50°C to 150°C, the MnZn ferrite of the present invention uses a composition with a high Curie temperature (low ZnO molar ratio). Thus, when using ferrite powder with a low ZnO molar ratio, the evaporation of Zn from the surface of the ferrite core is suppressed, so the composition difference between the surface and the inside of the core is small, and the deviation of the initial magnetic permeability and the incremental magnetic permeability is also small. Compared with the conventional MnZn-based ferrite for pulse transformers, the ferrite of the present invention has a composition with a low ZnO molar ratio, and therefore has the advantage of reduced deviation of magnetic properties.

[0101] Example

[0102] As the basic component of MnZn ferrite, Fe 2 O 3 , ZnO and Mn 3 O 4 (Composition ratio converted to MnO for processing) Each raw material powder was weighed so as to obtain the composition ratio shown in Tables 1 to 3. High-purity raw material powder was used as each raw material powder. These raw material powders were mixed and crushed in a ball mill for 16 hours, and then pre-calcined at 925°C × 3 hours in the air to obtain pre-calcined powder. Then, SiO was added to the pre-calcined powder so as to obtain the content shown in Tables 1 to 3. 2 、CaCO 3 、Co 3 O 4 、TiO 2 and Nb 2 O 5, in some examples shown in Table 3, V is further added 2 O 5 , crushed in a ball mill for 12 hours to obtain crushed powder. Then, polyvinyl alcohol was added to the crushed powder for granulation, and a pressure of 118 MPa was applied to form a ring-shaped core. Then, the formed body was loaded into a sintering furnace and sintered at a maximum temperature of 1350°C to obtain a sintered body sample (ferrite core) with an outer diameter of 30.5 mm×inner diameter of 19 mm×height of 6.5 mm.

[0103] Each ferrite core thus obtained was wound with 20 turns, and the magnetic properties were measured using a precision LCR meter E4980A (manufactured by Keysight Technologies). The initial magnetic permeability (no DC magnetic field applied: 0 A / m) was measured at 23°C and a frequency of 100 kHz. The incremental magnetic permeability (DC magnetic field applied: 25 A / m) was measured at -50°C, 0°C, 23°C, 50°C, 100°C, and 150°C at a frequency of 100 kHz. Tables 1 to 3 show the measurement results. Figure 1A , Figure 1B , Figure 2A to Figure 2E as well as Figure 3 A graph showing the measurement results.

[0104] Similarly, as shown in Table 4, changing the CaO addition amount and V 2 O 5 Addition amount to make ferrite core. Table 4, Figure 4A as well as Figure 4B The figures show the results of measuring the incremental permeability at a frequency of 100 kHz at temperatures of -50°C, 0°C, 23°C, 50°C, 75°C, 100°C, and 125°C while applying a DC magnetic field of 50 A / m.

[0105] The contents of P, B, S, Cl, K and other inevitable impurities were quantitatively determined according to JIS K 0102 (ICP mass spectrometry), and the total amount was confirmed to be 500 mass ppm or less. The measurement results are shown in the tables.

[0106] [Table 1]

[0107]

[0108] [Table 2]

[0109]

[0110] [Table 3]

[0111]

[0112] [Table 4]

[0113]

[0114] According to Table 1 and Figure 1A , Figure 1B The results of the invention examples 1 to 10 and the comparative examples 1 to 4 shown in the figure show that if Fe as the basic composition is Fe 2 O 3 When the conversion is 52.0 mol% or more and 53.6 mol% or less and Zn is 10.1 mol% or more and less than 13.0 mol% as ZnO, an incremental permeability of 2300 or more can be obtained in the temperature range of -50 to 150°C when a DC magnetic field of 25 A / m is applied.

[0115] According to Table 2 and Figure 2A The results of the invention examples 11 to 15 and the comparative examples 5 and 6 shown in the figure show that if Si as an auxiliary component is SiO 2 When converted to 30 mass ppm or more and 200 mass ppm or less, an incremental permeability of 2300 or more can be obtained in a temperature range of -50 to 150°C when a DC magnetic field of 25 A / m is applied.

[0116] According to Table 2 and Figure 2B From the results of the invention examples 11 and 16 to 19 and the comparative examples 7 and 8 shown, it can be seen that if the Ca as an auxiliary component is converted into CaO to be greater than 300 mass ppm and less than 1000 mass ppm, when a DC magnetic field of 25 A / m is applied, an incremental magnetic permeability of greater than 2300 can be obtained in the temperature range of -50 to 150°C.

[0117] According to Table 2 and Figure 2C The results of Inventive Examples 11 and 20 to 23 and Comparative Examples 9 and 10 shown in the figure show that if Co as an auxiliary component is Co 3 O 4 When converted to a range of 2100 mass ppm or more and 3500 mass ppm or less, an incremental magnetic permeability of 2300 or more can be obtained in a temperature range of -50 to 150°C when a DC magnetic field of 25 A / m is applied.

[0118] According to Table 2 and Figure 2D The results of the invention examples 11 and 24 to 26 and the comparative examples 11 and 12 shown in the figure show that when Ti as an auxiliary component is in the form of TiO 2 When converted to a range of 2500 mass ppm or more and 4000 mass ppm or less, an incremental magnetic permeability of 2300 or more can be obtained in a temperature range of -50 to 150°C when a DC magnetic field of 25 A / m is applied.

[0119] According to Table 2 and Figure 2EThe results of Inventive Examples 11 and 27 to 30 and Comparative Examples 13 and 14 shown in the figure show that when Nb as an auxiliary component is Nb 2 O 5 When converted to a range of 50 mass ppm or more and 500 mass ppm or less, an incremental permeability of 2300 or more can be obtained in a temperature range of -50 to 150°C when a DC magnetic field of 25 A / m is applied.

[0120] According to Table 3 and Figure 3 The results of Inventive Examples 31 to 35 and Comparative Example 15 shown in the figure show that when V as an auxiliary component is V 2 O 5 Converted to less than 500 mass ppm, when a DC magnetic field of 25A / m is applied, an incremental permeability of more than 2300 can be obtained in the temperature range of -50 to 150°C, which is similar to that without adding V. 2 O 5 Compared with the case where V is added 2 O 5 In the case of low temperature range and high temperature range, higher incremental permeability can be obtained.

[0121] According to Table 4 and Figure 4A From the results of Inventive Examples 36 to 39 and Comparative Example 16 shown, it can be seen that if Ca as an auxiliary component is 300 mass ppm or more and 1000 mass ppm or less in terms of CaO, an incremental permeability of 1000 or more can be obtained at 125°C when a DC magnetic field of 50 A / m is applied.

[0122] According to Table 4 and Figure 4B The results of Inventive Examples 39 to 46 and Comparative Example 17 shown in the figure show that when V as an auxiliary component is V 2 O 5 Converted to less than 500 mass ppm, when a DC magnetic field of 50A / m is applied, an incremental permeability of more than 1000 can be obtained at 125°C, which is similar to that without adding V. 2 O 5 Compared with the case where V is added 2 O 5 In the case of 125℃, a higher incremental permeability can be obtained.

[0123] (Example Deviation Investigation)

[0124] For Invention Example 47 and Comparative Example 18 shown in Table 5, ferrite pulverized powder was prepared in the same manner as described above, polyvinyl alcohol was added to the pulverized powder for granulation, a pressure of 118 MPa was applied, and a ring core was formed to form a molded body. Then, the molded body was placed in a sagger and loaded into a sintering furnace, and sintered at a maximum temperature of 1350°C to produce 100 sintered body samples (cores) with an outer diameter of 6.0 mm × an inner diameter of 3.0 mm × a height of 4.0 mm. For each core obtained, the initial magnetic permeability at 23°C and the incremental magnetic permeability when a DC magnetic field of 25 A / m was applied at -40°C were investigated by the above method, and the respective standard deviations σ were calculated based on the measurement results. Table 5 shows the results of the magnetic properties (initial magnetic permeability and incremental magnetic permeability as the average values ​​of 100 measurements) and the standard deviation σ.

[0125] Here, Comparative Example 18 has the same composition as Sample No. 1-5 (Inventive Example of Patent Document 1) of Patent Document 1. Inventive Example 47 and Comparative Example 18 have different initial permeabilities, but have almost the same incremental permeabilities when a DC magnetic field of 25 A / m is applied at -40°C.

[0126] [Table 5]

[0127]

[0128] As shown in Table 5, in the case of Inventive Example 47, the standard deviation σ of the initial magnetic permeability at 23°C and the incremental magnetic permeability when a DC magnetic field of 25 A / m is applied at -40°C are both smaller than those of Comparative Example 18. It can be seen from this that the composition with a low ZnO molar ratio of the present invention has a smaller deviation in magnetic properties than the conventional composition with a high ZnO molar ratio, and is more preferred.

[0129] Industrial Applicability

[0130] According to the present invention, a MnZn ferrite suitable for electronic components such as pulse transformers can be obtained, which has a high incremental permeability in a wide temperature range, that is, an incremental permeability of 2300 or more when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C. In addition, a MnZn ferrite with an incremental permeability of 1000 or more when a DC magnetic field of 50 A / m is applied at 125°C can be obtained. This can also be used for automotive applications and PoE power supply applications that require a wider temperature range than before.

Claims

1. A MnZn ferrite, which is composed of a basic component, an auxiliary component and inevitable impurities, When the total of Fe, Zn and Mn converted to Fe2O3, ZnO and MnO is taken as 100.0 mol%, The basic ingredients include: Fe: 52.0 mol% or more and 53.6 mol% or less in terms of Fe2O3; Zn: 10.1 mol% or more and less than 13.0 mol% in terms of ZnO; and Mn: remainder, Relative to the basic ingredients, the auxiliary ingredients include: Si: 30 mass ppm or more and 200 mass ppm or less in terms of SiO2; Ca: 300 mass ppm or more and 1000 mass ppm or less in terms of CaO; Co: 2100 mass ppm or more and 3500 mass ppm or less calculated as Co3O4; Ti: 2500 mass ppm or more and 4000 mass ppm or less calculated as TiO2; Nb: 50 mass ppm or more and 500 mass ppm or less calculated as Nb2O5; and V: 0 mass ppm or more and 500 mass ppm or less in terms of V2O5.

2. The MnZn-based ferrite according to claim 1, wherein: The content of V calculated as V2O5 is 50 mass ppm or more and 250 mass ppm or less.

3. The MnZn-based ferrite according to claim 1, wherein: The content of V calculated as V2O5 is 100 mass ppm or more and 500 mass ppm or less.

4. The MnZn-based ferrite according to claim 1 or 2, wherein: The MnZn-based ferrite has an incremental magnetic permeability of 2300 or more when a DC magnetic field of 25 A / m is applied in a temperature range of -50 to 150°C.

5. The MnZn-based ferrite according to claim 1 or 3, wherein: The MnZn-based ferrite has an incremental magnetic permeability of 1000 or more when a DC magnetic field of 50 A / m is applied at 125° C.

Citation Information

Patent Citations

  • Mn-Zn FERRITE

    JP2005236069A

  • MnCoZn FERRITE AND MAGNETIC CORE FOR TRANSFORMER

    JP2008143745A

  • MnZn-BASED FERRITE CORE AND METHOD FOR PRODUCING THE SAME

    JP2010173899A

  • MnZnCo-BASED FERRITE

    JP2010189247A

  • MnZnCo FERRITE CORE AND MANUFACTURING METHOD THEREFOR

    JP2010195596A